Progress in hydrogen fuel cell vehicles and up-and-coming technologies for eco-friendly transportation: an international assessment - Soleimani, Alireza; Hosseini Dolatabadi, Sayed Hamid; Heidari, Mehrdad; Pinnarelli, Anna; Mehdizadeh Khorrami, Behrouz; Luo, Yang; Vizza, Pasquale; Brusco, Giovanni (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2024)
The urgent need for sustainable energy solutions in light of escalating global energy demands and environmental concerns has brought hydrogen to the forefront as a promising renewable resource. This study provides a comprehensive analysis of the technologies essential for the production and operation of hydrogen fuel cell vehicles, which are emerging as a viable alternative to traditional combustion engine vehicles. It examines various fuel cell types, hydrogen storage methods, refueling logistics, and the role of batteries in fuel cell vehicles. The paper also explores the potential impact of advancements in artificial intelligence and quantum computing on the development of fuel cell vehicles. A global assessment reveals that South Korea (19,270) and the United States (12,283) are leading in the adoption of fuel-cell vehicles, particularly in the passenger car segment (82%), followed by buses (9.2%) and trucks (8.7%). The study highlights the challenges hindering fuel cell vehicle implementation, such as the need for consistent investment and collaboration among industry stakeholders to promote sustainable transportation systems. The analysis underscores the practicality of fuel cell vehicles, exemplified by models like the Toyota Mirai and Hyundai Nexo, which offer significant driving ranges and demonstrate the integration of advanced technologies. The paper discusses the environmental benefits of fuel cell vehicles, including their ability to operate with zero emissions when paired with renewable energy sources. Graphical Abstract